Computational Fluid Dynamics (CFD) Analysis of Archimedes Wind Turbine - Mohamad Raffi, Mohamad Faizal; Mohd, Sofian (Progress in Aerospace and Aviation Technology, 2024)
Windmills, or wind turbines, generate wind energy and serve as a viable substitute for fossil fuels. This study mainly focuses on the Archimedes wind turbine, a novel horizontal-axis wind turbine design inspired by Archimedes' screw pump. Computational Fluid Dynamics (CFD) analysis plays a crucial role in enhancing the turbine's effectiveness, providing insights into its performance. This study investigated the performance of the Archimedes wind turbine with respect to pitch, opening angle, and wind speed variation, utilizing SolidWorks for three-dimensional modeling and ANSYS Fluent for CFD analysis. Additionally, wind turbine comparative analysis was conducted to evaluate the power and torque coefficients of the Archimedes wind turbine against the Savonius and Helical Savonius wind turbines at various wind speeds. Essentially, the study's results showed that increasing the pitch and opening angle of the Archimedes wind turbine positively impacted the power coefficient and torque coefficient, resulting in improved turbine performance. When increasing the pitch from 600 mm to 2000 mm, the maximum C_p and C_t achieved were 0.2013 and 0.2577, respectively, at 1400 mm pitch. Furthermore, when increasing the opening angle from 15° to 75°, the maximum C_p and C_t achieved were 0.2290 and 0.2937, respectively, at a 60° opening angle. The Archimedes turbine consistently outperformed the Savonius and Helical Savonius wind turbines, indicating its potential for wind energy applications. However, the Helical Savonius has approximately similar performance to the Archimedes wind turbine. Therefore, this study provided valuable insights into the performance of the Archimedes wind turbine through CFD analysis. The findings contributed to the development of more efficient wind energy technology, addressing environmental concerns and promoting sustainable energy solutions.